HUBUNGAN POLA ASUH ORANG TUA DAN KONFORMITAS TEMAN SEBAYA DENGAN PERILAKU BULLYING PADA REMAJA DI KOTA KUPANG - Feoh, Fepyani Thresna; Muskananfola, Istha Leanni (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Bullying can have a negative impact on both the victim and the perpetrator. Victims of bullying tend to experience anxiety, trauma, fear of meeting other people, even low self-esteem and suicide attempts, while bullies continue to feel selfish and feel the greatest. There are many factors that cause teenagers to engage in bullying behavior, including parenting patterns and peer conformity. The aim of this research is to analyze the relationship between parenting styles and peer conformity with bullying behavior among teenagers at SMP Negeri 10 Kupang City. This research is a correlation analytical research conducted on 76 students. Data were collected using a questionnaire and tested using the Chy-square test. The results of the research prove that there is a relationship between peer conformity and bullying behavior among teenagers at SMP Negeri 10 Kupang City with a p value of 0.000. Meanwhile, parenting style does not have a significant relationship between parenting style and bullying behavior among teenagers at SMP Negeri 10 Kupang City with a ρ value of 0.097.